OUTCOME OF OPEN INTERLOCKING NAILING IN CLOSED FRACTURE SHAFT OF FEMUR - Adeel, Muhammad; Zardad, Shoaib; Jadoon, Shandana Mustafa; Younas, Muhammad; Shah, Usman (Journal of Ayub Medical College Abbottabad, 2020)
Background: Various treatment modalities have been used in treating femoral shaft fractures, i.e., open intramedullary nailing, plating and external fixators but these does not always produce stable fixation and there is increased risk of infection, closed locked intramedullary nailing technique has being the gold standard and is a routine procedure but it requires proper orthopedic operation table with traction apparatus and the use of image intensifier. The use of open interlocking nailing technique doesn't require any special orthopaedic table nor it requires use of Image intensifier. The objective of this study is to find out and determine the frequency of fracture union and wound infection in open reamed interlocking nailing of close fractures of shaft of femur. Methods: This study included fifty-eight patients from either gender, above 14 years of age with closed femoral shaft fracture presenting within 2 weeks. Data was collected on Performa about gender, age, address, date of fracture, date of operation and discharge, type of fracture and follow-up visits. Results: Mean age of the patients were 31.24±8.662. According to Winquist & Hansen, femur shaft fractures were divided into four types. Type I were found in the 16(27.6%), Type II in 21 (36.2%), Type III in 12 (20.7%) and Type IV in 9 (15.5%). Total number of fracture union with regard to Winquist & Hensen Classification of fracture shaft femur were, Type I, 14 (24.1%), Type II, 21 (36.2%), Type III, 12 (20.7%), Type IV, 8 (13.8%) respectively while the rest 3 (5.2%) were found in non-union. Total number of fracture union with regard to gender of the patients were, 41 (70.7%) males and 14 (24.1%) were females while the rest 3 (5.2%) patients fracture union has not occurred. Fracture union was found in 55 (94.8%) out of 58 patients; while fracture union had not occurred in 3 (5.2%) out of 58 patients. The total number of patients who developed wound infection following surgery were 5 (8.6%) out of 58 patients; while the non-infected patients were 53 (91.4%) out of 58 patients. Conclusion: The open interlocking nailing technique for close fractures shaft of femur without the use of image intensifier achieved excellent results in terms of fracture union. Results obtained are mostly similar to the results of close interlocking nailing and it also requires less expertise, recourses and without the use of image intensifier. Keywords: Close Femoral Shaft Fracture; Open Interlocking nail